Information and communication technology in home-based rehabilitation – a discussion of possibilities and challenges. (2nd January 2023) - Nyman, Anneli; Zingmark, Magnus; Lilja, Margareta; Guidetti, Susanne
Abstract: Background: Information and communication technology (ICT) has been proven to have effect in terms of providing alternative ways to deliver rehabilitation services. The intention with this paper is to serve as a foundation for discussions regarding the future development, design, and delivery of home-based rehabilitation, including ICT. Aim: To reflect on and discuss the possibilities and challenges of using ICT in home-based rehabilitation services. Method and material: We use experiences and results from various projects to reflect on and discuss possibilities and challenges related to the use of ICT in home-based rehabilitation. Findings and discussion: We exemplify how ICT present new possibilities that can increase the quality of the rehabilitation process and improve access to services. We reflect on some challenges in the use of ICT, related to non-user-friendly solutions, to the specific rehabilitation situation, and a lack of technical support. At an organisational level, readiness to use ICT can impact the extent to which new solutions are integrated into practice. Conclusion: We emphasise that ICT has the potential to develop and improve service delivery and contribute to increased quality and accessibility of home-based rehabilitation.